THE EFFECT OF THE BTS AS A BRAND AMBASSADOR AND SALES PROMOTION ON THE IMPULSE BUYING OF TOKOPEDIA CUSTOMERS ALL OVER INDONESIA IN THE TOKOPEDIAXBTS 12TH ANNIVERSARY EDITION EVENT - Rif'ah Malia; Sonja Andarini (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
Modern humans are starting to take advantage of technological sophistication and shifting human behavior into opportunities that can be used as business fields, one of which is Tokopedia. More and more similar businesses make companies need to make strategies in order to survive in the face of competition, some of which are by using brand ambassadors and making sales promotions. This study aims to determine and analyze the effect of Brand Ambassador and sales promotion on Impulse Buying of Tokopedia customers at the TokopediaxBTS 12th Anniversary Edition Event. This type of research is descriptive analysis using multiple linear regression analysis. The sampling technique used is non-probability sampling with an accidental sampling approach. The results of this study indicate that simultaneously, the brand ambassador variable and sales promotion have a positive and significant effect on impulse buying. Partially, the brand ambassador variable has a positive and significant effect on impulse buying while the sales promotion variable has a negative and insignificant effect on impulse buying.